The Jungle Book - Kipling, Rudyard (London Readings, 2016)
Adopted by a family of wolves in India, Mowgli lives by the Law of the Jungle until he ventures into the village to meet the mysterious animals called humans.
Keywords: Jungle animals -- Feral children -- Adventure stories, English